Shame and the Dilemma of Human Destructiveness - Baum, Scott (Bioenergetic Analysis, 2019)
This article examines the phenomenon of shame and related states from clinical and theoretical perspectives within Bioenergetic Analysis. Links are made to the general problem of human destructiveness and to the specific ways that shame is used destructively in relationships and families. The author’s personal struggle is used to illuminate one approach to living the reality of destructive shame.